MİKROBİYOLOJİ VE KLİNİK MİKROBİYOLOJİ ANABİLİM DALI DERİN MİKOZ LABORATUARINDA 01 NİSAN 1999- 27 MART 2001 ARASINDA AYRILAN MAYA VE KÜFLERİN TÜR DAĞILIMLARI VE DUYARLILIK PATERNİ - KANTARCIOĞLU, A. Serda; YÜCEL, Ayhan (Cerrahpaşa Medical Journal, 2019)
Background and Design.- The purpose of this study was to characterize the species distribution and antifungal susceptibility patterns of yeast and mold strains isolated at deep mycoses laboratory, Department of Microbiology and Clinical Microbiology. The species distribution and antifungal susceptibility patterns of the clinically significant yeast and mold isolates recovered from deep mycoses suspected patients. specimens over a two year period were determined against amphotericin B, fluconazole, itraconazole, ketoconazole, miconazole, flucytosine and terbinaphyne using the M27-A and M38-P reference methods. Results.- A total of 146 yeast and 12 mould strains were isolated. C. albicans strains was %66.4 (97/146), and non-albicans Candida species were %33.6 (49/146). The frequency of various yeast species identified was Candida catenulata 1 (0.7%), C. glabrata 6 (4.1%), C.kefyr 4 (2.7%), C. krusei 6 (4.1%), C. lipolytica 3 (2.0%), C. lusitaniae 1 (0.7%), C.parapsilosis 8 (5.5%), C. rugosa 2 (1.4%), C. tropicalis 12 (8.2%), M. furfur 1 (0.7%), T.beigelii 3 (2.0%), Cryptococcus neoformans 2 (1.4%). The frequency of mold species identified Aspergillus flavus 4 (33.3%), A. fumigatus 2 (16.6%), A. niger 3 (25%), A.versicolor 1 (8.3%), Cladosporium cladosporioides 1 (8.3%), Scopulariopsis candida 1 (8.3%) and Cladosporium sp 1 (8.3%). Resistance to fluconazole (MIC > or = 64 micrograms/ml) as per NCCLS criteria was observed in 21 C. albicans (21.6%), 19 non-albicans Candida strains (38.8%); resistance to itraconazole (MIC > or = 1 micrograms/ml) in 31 C. albicans (32.2%), 15 nonalbicans Candida strains (30.6%) and resistance to flucytosine (MIC > or = 32 micrograms/ml) in 5 C. albicans (5.1%), 7 non-albicans Candida strains 7 (14.3%). Conclusion.- The present study indicates that Candida sp. are emerging as important pathogens in immunocompromised patients and the tendency of yeasts to develop resistance to antifungal agents and the appearance of species/strain specific susceptibility of molds, in vitro tests seem to be useful for patient management.